Lipase Inhibitors for Obesity: A Review - Liu, Tian-Tian; Liu, Xiao-Tian; Chen, Qing-Xi; Shi, Yan (Biomedicine & pharmacotherapy, 2020)
•The role of pancreatic lipase inhibitor in lipid metabolism is elaborated.•The existing microbial sources of high activity and high yield lipase was summarized, to provide reference for researchers.•Lipase inhibitors from natural products was summarize for readers’ reference.•The manuscript has summarized the research status of pancreatic lipase inhibitor on anti-obesity and provided new ideas to solve the bottleneck problem. With the rapid increase in the population of obese individuals, obesity has become a global problem. Many kinds of chronic metabolic diseases easily caused by obesity have received increasing attention from researchers. People are also striving to find various safe and effective treatment methods as well as anti-obesity medicines. Pancreatic lipase (PL) inhibitors have received substantial attention from researchers in recent years, and PL inhibitors from natural products have attracted much attention due to their structural diversity, low toxicity and wide range of sources. They have been used in the intestinal tract, blood, and the central nervous system with no side effects, and these advantages could lead to a new generation of diet pills or health care products with great development potential. This article is mainly aimed at discussing the research of obesity drug treatment with PL inhibitors and offers a brief review of related properties and the use of PL inhibitors in the field of weight loss.